The degree of agility in a technology company’s strategy, management, and leadership - Vanharanta, Hannu; Kantola, Jussi; Markopoulos, Evangelos; Salo, Markku (De Gruyter Open, 2018)
Agility is a concept and practice with significant importance in managing and leading added value in products, services, projects, and organizations, although it’s usage can also be very risky due to its degree of fuzziness, if not properly understood and defined. This research re-defines agility, emphasizes the need for ontologies for its management and leadership applications and uses a new type of fuzzy logic-based software to measure the degree of agility inside a technology company. In our agility research, various definitions of agility were first gathered and presented for the creation of an agility ontology through a mind map, revealing the main characteristics of agility. Then as part of the Co-Evolute theory and methodology, the first agility ontology was developed as well as the first software application that evaluates the degree of agility in an organization. The application includes statements on which the respondents give opinions in their situation concerning the current and future desired states of agility and its importance in an evaluative way. Today the application has been fully tested in the real world and we have obtained the first test results. The positive verification and validation of the method are shown in this article.
Keywords: agility; application; innovativeness; leadership; management; ontology; validation; verification; fi=Tuotantotalous|en=Industrial Management|